IMPLEMENTASI DAN FAKTOR-FAKTOR YANG MEMENGARUHI PETERNAK DALAM MEMILIH BERUSAHA TERNAK AYAM BROILER MELALUI POLA KEMITRAAN INTI PLASMA DI KOTA KENDARI - Muhammad Rudiawan; Bahari Bahari; Muh. Arief Dirgantoro (Universitas Halu Oleo, 2019)
This study aims to analyzing the implementation of broiler chicken business contracts, analyzing the factors that influence breeders to choose broiler breeding businesses with a partnership pattern, and comparing the finances between broiler business farmers in partnership with independent pattern broiler chicken businesses Kendari by using 66 respondents determined through the census method. Data is estimated by; descriptive analysis, binary logistic regression analysis and analysis of independent sample t test. The results showed that: the level of implementation of chicken business contracts in Kendari City depends on the high category, which means that the implementation of the contract has been going well, but some attributes still need to be improved, including three variables related to farmers to choose a broiler chicken business through a partnership pattern, namely; the level of income of independent farmers is higher than the level of income of farmers in the partnership pattern per maintenance cycle. However, the level of income of farmers per year from the two groups was not significantly different.Keywords: breeders; broilers chickens; partnership patterns; nucleus-plasma